The Smart City Hospitality Framework: Creating a foundation for collaborative reflections on overtourism that support destination design. (March 2021) - Koens, Ko; Melissen, Frans; Mayer, Igor; Aall, Carlo
Abstract: This paper introduces the Smart City Hospitality Framework, which could serve as the foundation for a destination-design-driven approach to urban tourism governance and dealing with overtourism issues. This conceptual framework is purposely designed to stimulate collaborative (informed) reflections on overtourism and urban tourism development that could support system analyses, problem structuring and development of transition agendas and pathways within the context of turning urban tourism into a transition arena that contributes to setting in motion a sustainability transition at city level. It merges the dimensions of sustainable development (environmentally responsible and equitable economic development) and city hospitality (the extent to which the city acts as a good 'host' to all its 'guests', including residents and businesses). Resilience resides at its centre to highlight the temporal aspects of these dimensions, and their interdependencies. To show how this framework can serve as the foundation for destination design efforts in practice, a short description of (experiences with) serious game-playing sessions that employ its logic in six European cities is provided. Highlights: Collaborative reflections can be a way to improve governance practices. Introduces a framework for a destination-design-driven approach to tourism governance. Gives an example of an analogue smart tool for eliciting reflective conversations. Sustainable development, smart hospitality and resilience can be combined. Design thinking is key to setting sustainability transitions in motion.